IDENTIFICATION OF MESO-SCALE EDDY CURRENTS IN THE SULAWESI SEA DURING THE 2015 EL NIÃ±O-SOUTHERN OSCILLATION (ENSO) EVENT - Kinasih Anggitan Mahanani, Afifa
In this study, sea level anomaly (SLA) parameters and geostropic current components are used to identify the characteristics of meso-scale eddy currents in Sulawesi Waters in 2015 (El Niño) which will then be compared with La Niña conditions in 2011 and normal conditions in 2013. The method used is the Okubo-Weiss parameter coupling method with closed contour SLA. From the data processing, a total of 137 cyclonic eddy currents and 206 anticyclonic eddy currents were detected in the three years studied. The number of eddy currents during the El Niño event was detected the least compared to normal and La Niña years. La Niña years had the highest number of eddy currents detected. The longest-lived eddy currents were detected in El Niño years with a duration of 59 days. Changes in SLA in each ENSO condition affect the number and age of the eddy. In all years eddy currents with anticyclonic type are more detected than cyclonic type. The eddy current formation area is generally located in the north of Sulawesi Island and the central part of the Sulawesi Sea.